Salesperson Perceptions of Ethical Behaviors: Their Influence on Job Satisfaction and Turnover Intentions - Pettijohn, Charles (Journal of business ethics, 2008)
In the academic world, research has indicated that “good ethics is good business.” Such research seems to indicate that firms, which emphasize ethical values and social responsibilities, tend to be more profitable than others. Generally, the profitability is credited to the firm’s positive relationships with its customers, reduced costs of attempting to rebuild a tarnished image, ease of attracting capital, etc. The research conducted in this study evaluated salespeople’s perceptions of the ethics of businesses in general, their employer’s ethics, their attitudes as consumers, and the relationships existing between these perceptions and the sale force’s job satisfaction and turnover intentions. The results show a positive relationship existing between salesperson perceptions of business ethics, his/her employer’s ethics, consumer attitudes, and the salesperson’s job satisfaction and reduced turnover intentions.